2007
DOI: 10.1104/pp.107.099903
|View full text |Cite
|
Sign up to set email alerts
|

The COMATOSE ATP-Binding Cassette Transporter Is Required for Full Fertility in Arabidopsis

Abstract: COMATOSE (CTS) encodes a peroxisomal ATP-binding cassette transporter required not only for b-oxidation of storage lipids during germination and establishment, but also for biosynthesis of jasmonic acid and conversion of indole butyric acid to indole acetic acid. cts mutants exhibited reduced fertilization, which was rescued by genetic complementation, but not by exogenous application of jasmonic acid or indole acetic acid. Reduced fertilization was also observed in thiolase (kat2-1) and peroxisomal acyl-Coenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 93 publications
(101 reference statements)
0
80
0
4
Order By: Relevance
“…Measurements were made using NIH Image software. comatose alleles of PXA1, the ABC transporter likely to bring IBA into the peroxisome (Zolman et al, 2001b), display a stamen filament elongation delay that is rescued by NAA application (Footitt et al, 2007), suggesting that the auxin required for filament elongation (Cecchetti et al, 2008) is low in this tissue. Similarly, the ibr1 ibr3 ibr10 short-root-hair phenotype was fully rescued by exogenous IAA and NAA, but only partially rescued by the auxin transport inhibitors NPA or TIBA, consistent with the possibility that active auxin levels are low in root hair cells of this mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were made using NIH Image software. comatose alleles of PXA1, the ABC transporter likely to bring IBA into the peroxisome (Zolman et al, 2001b), display a stamen filament elongation delay that is rescued by NAA application (Footitt et al, 2007), suggesting that the auxin required for filament elongation (Cecchetti et al, 2008) is low in this tissue. Similarly, the ibr1 ibr3 ibr10 short-root-hair phenotype was fully rescued by exogenous IAA and NAA, but only partially rescued by the auxin transport inhibitors NPA or TIBA, consistent with the possibility that active auxin levels are low in root hair cells of this mutant.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular identity of the core b-oxidation pathway components and their physiological role in FA catabolism in postgerminative seedling growth in oilseeds are now well established (Graham, 2008;Theodoulou and Eastmond, 2012). Physiological understanding of b-oxidation in mature plant tissues has been defined in dark-induced (Kunz et al, 2009) or natural (Yang and Ohlrogge, 2009) senescence, reproductive development (Rylott et al, 2003;Footitt et al, 2007aFootitt et al, , 2007b, with respect to the biosynthesis of auxin (Strader and Bartel, 2011) and jasmonate (Goepfert and Poirier, 2007), and during storage TAG production (Slocombe et al, 2009;Kelly et al, 2013). The results of this study provide new insights into the regulation of the peroxisomal b-oxidation pathway and its role in membrane lipid homeostasis in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that, besides a fast ATP-driven transport, OPDA also may enter peroxisomes by a passive route. Inside peroxisomes, an unknown critical threshold of JA exists, and levels below this threshold can affect fertility in different ways (McConn and Browse, 1996;Footitt et al, 2007). Generally, pollen defects become obvious by a significant deviation from Mendelian genetics.…”
Section: Discussionmentioning
confidence: 99%